Broadband interference excision for software-radio spread-spectrum communications using time-frequency distribution synthesis. - Lach, S.R (IEEE Journal on selected areas in communications)
A new method is introduced for interference excision in spread-spectrum communications that is conducive to software-radio applications. Spare processing capacity in the receiver permits the use of time-frequency techniques to synthesize a nonstationary interference from the time-frequency domain using least squares methods. The synthesized signal is then subtracted from the incoming data in the time domain, leading to jammer removal and increased signal-to-interference-and-noise ratio at the input of the correlator. The paper focuses on jammers with constant modulus that are uniquely described by their instantaneous frequency characteristics. With this a priori knowledge, the jammer signal amplitude is restored by projecting each sample of the synthesized signal to a circle representing its constant modulus. With the phase matching provided by the least squares synthesis method and amplitude matching underlying the projection operation, a significant improvement in receiver performance/bit-error rates is achieved over the case where no projection is performed. Software-radio aspects including computational complexity and processing modes are also discussed